Windows on the whole world. (Economist, 1997)
Microsoft's new Windows CE may become the world's most ubiquitous operating system. CE, a subset of Windows 95, supports a new array of powerful processors; runs color screens; comes with a pocket version of PowerPoint, a program used to prepare executive presentations; and offers much faster downloads of data from the desktop. Microsoft wants cable operators to use CE in their set-top boxes to bring the Internet to the television, although most companies would prefer an open standard. If cable firms do not succumb, Microsoft intends to use the technology in one of its own companies, WebTV: By 1998, WebTV's box will be running CE and Microsoft's Internet explorer browser.